A New Surgical Technique for Spontaneous Esophagopleural Fistula after Pneumonectomy: Cervical Esophagogastrostomy via Presternal and Subcutaneous Route, Using a Thoracic Esophageal Mucosal Stripping - Kim, Jae Jun; Park, Jae Kil; Moon, Seok Whan; Park, Khun (The Thoracic and Cardiovascular Surgeon, 2013)
We report a new surgical technique for spontaneous esophagopleural fistula after pneumonectomy. A 67-year-old man underwent right pneumonectomy for tuberculosis-destroyed lung 30 years previously and a right Eloesser window for empyema without any evidence of fistula 4 years previously. He presented to our hospital for food material spillage out of the Eloesser window when he was eating. The esophagopleural fistula was observed from the upper thoracic esophagus to the right postpneumonectomy dead space. He underwent left cervical esophagogastrostomy via a presternal subcutaneous route, using thoracic esophageal mucosal stripping. He was discharged without complications on postoperative day 12.
Keywords: esophagopleural fistula; pneumonectomy; mucosal stripping